AI-adoption attitudes in Southern Africa’s higher education sector: A pilot survey using the capability, opportunity, motivation and behaviour (COM-B) model - Mark E. Patterson; Johan Breytenbach; Ian Coffman (The African Journal of Information and Communication, 2025)
Artificial intelligence (AI) drives innovation but faces numerous potential challenges to adoption. This pilot survey applied the capability, opportunity, motivation and behaviour (COM-B) model to examine AI adoption attitudes in the Southern African higher education sector. The study sought to evaluate the extent to which the COM-B framework, rooted in behavioural science, can generate AI-adoption insights that would be complementary to insights generated by established information systems (IS) adoption models, such as the technology acceptance model (TAM) and the unified theory of acceptance and use of technology (UTAUT). Potential facilitators and barriers with respect to adoption of AI tools adoption were mapped against COM-B domains to develop a 10-point Likert-type scale survey that was piloted with 33 individuals working in the Southern African higher education sector. The findings identified key facilitators of AI as adequate technological infrastructure, readiness to address clients’ ethical concerns, and beliefs that AI tools benefit clients. The dominant barrier identified was clients’ potential ethical concerns regarding AI use in decision-making.